1994
DOI: 10.4039/ent1261105-5
|View full text |Cite
|
Sign up to set email alerts
|

INTRA- AND INTER-CROWN DISTRIBUTION OF THE EASTERN SPRUCE GALL ADELGID, ADELGES ABIETIS (L.), ON YOUNG WHITE SPRUCE

Abstract: Intra- and inter-crown distribution of eastern spruce gall adelgid, Adelges abietis (L.) (Homoptera: Adelgidae), on young white spruce, Picea glauca (Moench) Voss., was studied at three sites in New Brunswick, Canada. Within a branch, the majority of galls were found on lateral shoots. Similar distributions of galls within trees were observed regardless of whether 20 or 30 lateral shoots or all shoots on a branch were sampled. Gall densities were highest on mid-crown branches of open-grown trees 1–4 m tall and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
15
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 10 publications
4
15
0
Order By: Relevance
“…Gall densities were highest in the mid crown, supporting results of a previous study (Fidgen et al 1994). Given that shoot length in conifers decreases basipetally (Fay & Whitham 1990;Carroll & Quiring 1993), the avoidance of the most and least vigorous parts of the tree suggests that a parabolic relationship exists between insect abundance and performance and shoot length.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Gall densities were highest in the mid crown, supporting results of a previous study (Fidgen et al 1994). Given that shoot length in conifers decreases basipetally (Fay & Whitham 1990;Carroll & Quiring 1993), the avoidance of the most and least vigorous parts of the tree suggests that a parabolic relationship exists between insect abundance and performance and shoot length.…”
Section: Discussionsupporting
confidence: 86%
“…The only other study to report a similar result was Hartley & Lawton (1992), where the survivorship of one of two species of gallers was negatively correlated to the N content within its gall. Hartley (1998) recently reported that many insect galls contain higher levels of phenols and lower levels of nitrogen than adjacent ungalled tissues, and suggested that phenols may be synthesized at a higher rate in galls than in ungalled tissues.Gall densities were highest in the mid crown, supporting results of a previous study (Fidgen et al 1994). Given that shoot length in conifers decreases basipetally (Fay & Whitham 1990;Carroll & Quiring 1993), the avoidance of the most and least vigorous parts of the tree suggests that a parabolic relationship exists between insect abundance and performance and shoot length.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…The presence of most scale insects is readily observed on the plant surface in the form of galls or wax secretions, but the quantiÞcation of the insects is often complicated by their small size and the propensity for groups of them to remain concealed beneath the plant tissue or wax secretion (Speight 2005). Sampling methodologies for scale insects may be intended to provide whole plant assessments of bark-infesting scale species such as the balsam wooly adelgid, Adelges piceae (Ratzeburg) (Hemiptera: Adelgidae) (Amman 1969) or may be based on counting readily observable galls including those of the Cooley spruce gall adelgid, Adelges cooleyi (Gillette) (Lasota and Shetlar 1986) and the eastern spruce gall adelgid, Adelges abietis L. (Fidgen et al 1994). To date, levels of beech scale (Cryptococcus fagisuga Lindinger) infestation or severity of the associated beech bark disease (BBD) have been assessed using qualitative classiÞcation schemes (Houston et al 1979, Twery and Patterson 1984, GrifÞn et al 2003, Wiggins et al 2004).…”
mentioning
confidence: 99%
“…of shoots of white spruce galled by the adelgid Adelges abietis, according to tree height and branch whorl. From Fidgen et al (1994). calculated in relation to the number of sampled shoots in each size (diameter) class. The incidence of galls themselves does not necessarily provide estimates of insect abundances since in many species of gall-inducing insects, several individuals may inhabit one gall.…”
Section: Detectionmentioning
confidence: 99%